2016
DOI: 10.1007/s12013-016-0725-x
|View full text |Cite
|
Sign up to set email alerts
|

ZFX Facilitates Cell Proliferation and Imatinib Resistance in Chronic Myeloid Leukemia Cells

Abstract: Zinc finger protein, X-linked (ZFX) mediates the development and progression of human cancers. However, its potential role in chronic myeloid leukemia (CML) is still unknown. The ZFX expression was significantly increased in CML patients and cell lines. Based on loss-of-function experiments in CML cells, we found that knockdown of ZFX expression impaired cell proliferation and induced mitotic arrest in G0/G1 stage and apoptosis. In addition, ZFX silencing sensitized CML cells to imatinib treatment. Further, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“… 19 ZFX promoted the proliferation and elevated the drug resistance of chronic myeloid leukemia cells to imatinib. 33 As for TNBC, CCAT1 contributed to the development of TNBC through upregulating ZFX via acting as a sponge of miR‐218, 20 indicating the oncogenic role of ZFX in TNBC. ZFX was identified as a target of miR‐1296.…”
Section: Discussionmentioning
confidence: 99%
“… 19 ZFX promoted the proliferation and elevated the drug resistance of chronic myeloid leukemia cells to imatinib. 33 As for TNBC, CCAT1 contributed to the development of TNBC through upregulating ZFX via acting as a sponge of miR‐218, 20 indicating the oncogenic role of ZFX in TNBC. ZFX was identified as a target of miR‐1296.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ZFX participates in drug resistance in hepatocellular carcinoma (24,25). The results of our previous study also demonstrated that ZFX may be involve in the regulation of cell proliferation and imatinib resistance in CML (26). Thus, the present study investigated the effects and mechanisms of HHT facilitating imatinib sensitivity in K562 human CML cells.…”
Section: Introductionmentioning
confidence: 55%
“…The results of our previous study demonstrated that ZFX silencing may inhibit CML cell growth through the PI3K/AKT pathway (26). To test whether the effect of HHT on CML cells was associated with ZFX expression, RT-qPCR and western blot analyses were performed; the results revealed that the mRNA and protein expression levels of ZFX were dose-dependently decreased by HHT treatment for 24 h in K562 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Elsewhere in the hematopoietic system, ZFX has been reported as important for BCRinduced B-cell proliferation and B-cell survival (8). ZFX was also found to be an inhibitor of the differentiation of acute T-lymphoblastic leukemia and myeloid leukemias (9), and important for imatinib resistance and proliferation of chronic myeloid leukemia cells (10).…”
Section: Discussionmentioning
confidence: 99%